Performances of a Spark Ignition (SI) engine fuelled with Liquefied Petroleum Gas (LPG) using Liquid Sequential Injection (LSI) technique - Tukiman, Mohd Mustaqim (2017)
The increment of fuel cost and environmental pollutions from transportation sector has created interest on alternative fuels particularly in spark ignition (SI) engines. One of the seen potential of alternative fuel is Liquefied Petroleum Gas (LPG). LPG has a research octane number higher than gasoline and low carbon to hydrogen ratio content, thus the LPG has the potential to give more power in SI engines and to reduce exhaust emissions. An experimental work was conducted on a 1.6 Liters, 4-cylinder engine from a Proton Gen 2 (S4PH), equipped with gasoline Multi Point Port Injection (MPI) system. The engine was retrofitted with LPG Liquid Sequential Injection (LSI) and a piggy-back system emulated the stock Electronic Control Unit (ECU). The engine was tested in steady state conditions, which are based on engine speed from 1500rpm to 4000rpm with increment of 500rpm. The Throttle Position (TP) was varied at four different levels that were 25%, 50%, 75% and 100% for every engine speed tested. The findings from the experiment showed that the liquid phase LPG increased brake power (BP) and brake torque (BT) in the range of 3% to 7%. The brake specific fuel consumption (BSFC) of LPG at low engine speed (1500rpm to 2500rpm) was reduced in the range from 21% to 52%. Meanwhile, at higher engine speed (3000rpm to 4000rpm) the LPG BSFC increased in average between of 3% to 57%. The carbon monoxide (CO) exhaust emission was reduced in the range of 2% to 19% when using LPG. The carbon dioxide (CO2) is also lower than gasoline in average between 9% and 18%. The hydrocarbon (HC) emission from LPG was increased in the range of 40% to 70%, and concentration of NOx emission was increased in average of 60% in comparison with gasoline. As a conclusion, the LPG LSI system used in S.I engine is more effective than gasoline at low engine speed condition due to low fuel consumption and emission.